ALKYLBENZENE FRACTION AS A WASTE CONVERSION PRODUCT – A PROSPECTIVE COMPONENT FOR THE PRODUCTION ENVIRONMENTAL AVIATION GASOLINES - BOICHENKO, SERGII; SHKILNIUK, IRYNA; KUBERSKYI, IHOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article is devoted to the results of experimental investigations on the properties of pyrolysis liquids from polyethylene and textile waste. The most suitable raw material for obtaining gasoline components was polymer waste – 33% of the gasoline fraction yield. The qualitative composition of the pyrolysate from polymer waste indicates its high anti-knock properties. Due to the content of ballast components in the gasoline fraction, it is not rational to use it directly for the preparation of gasolines. Therefore, the C7–C10 alkylbenzene fraction was extracted from it, which showed high efficiency as an alternative high-octane additive (105 octane number) for the production of environmentally friendly aviation gasolines without tetraethyl lead (TEL, Pb(CH₃CH₂)₄). The obtained results confirmed the hypothesis of a circular approach to obtaining the alkylbenzene fraction of the gasoline fraction of pyrolysis liquid from polyethylene waste as an alternative additive (component, additive) for the production of environmentally friendly aviation gasolines. This mixture is a good alternative to the standard high-octane component – alkylate. The results of the research demonstrated the high efficiency of the alkylbenzene fraction as part of a model laboratory mixture of components, the quality of which meets the requirements of ASTM D 6227 (for aviation gasoline grade Grade UL87). Our work also creates a fundamental basis for further research in the field of circular economy and obtaining alternative components (additives) for the production of composite (reformulated) aviation and automotive gasolines without TEL content.